Catching the bound states in the continuum of a phantom atom in graphene - Guessi, L. H. [UNESP]; Machado, R. S. [UNESP]; Marques, Y. [UNESP]; Ricco, S. [UNESP]; Kristinsson, K.; Yoshida, M. [UNESP]; Shelykh, I. A.; Souza, M. de [UNESP]; Seridonio, A. C. [UNESP] (Amer Physical Soc, 2015)
We explore theoretically the formation of bound states in the continuum (BICs) in graphene hosting two collinear adatoms situated at different sides of the sheet and at the center of the hexagonal cell, where a phantom atom of a fictitious lattice emulates the six carbons of the cell. We verify that in this configuration the local density of states near the Dirac points exhibits two characteristic features: (i) a cubic dependence on energy instead of a linear one for graphene as found in New J. Phys. 16, 013045 (2014), and (ii) the formation of BICs as an aftermath of a Fano destructive interference assisted by the Coulomb correlations in the adatoms. For the geometry where adatoms are collinear to carbon atoms, we report an absence of BICs.